Development of Xin-Yang 信仰 scale: understanding spirituality among Chinese college students. Issue 2 (3rd April 2022) - Li, Shengnan; Duan, Changming; Li, Fenglan
ABSTRACT: The current study pursued a scale development process to understand spirituality among Chinese college students. From definition to item development, Chinese college students' view and experiences were used as the bases. The validation process involved 1, 207 college students from five different provinces, autonomous regions, and direct-controlled municipalities in China. Item factor analysis and structural equation modelling were performed. The study resulted in a Xin-Yang scale (Xin-Yang 信仰 is deemed as a conceptually similar concept to spirituality in Western cultures and is familiar to the Chinese college students), consisting of three factors: characteristics, mental guidance, and relationship to others. Satisfactorily, psychometric qualities were established. Furthermore, for Chinese college students, Xin-Yang信仰 is shown to be significantly and positively correlated with life satisfaction, self-esteem, and self-efficacy, and negatively with psychological symptoms. In addition, Xin-Yang 信仰is significantly and positively correlated with a Western spirituality measure. Limitations and implications were discussed.